2016
DOI: 10.1016/j.joca.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis year in review 2015: mechanics

Abstract: Motivated by the conceptual framework of multi-scale biomechanics, this narrative review highlights recent major advances with a focus on gait and joint kinematics, then tissue-level mechanics, cell mechanics and mechanotransduction, matrix mechanics, and finally the nanoscale mechanics of matrix macromolecules. A literature review was conducted from January 2014 to April 2015 using PubMed to identify major developments in mechanics related to osteoarthritis (OA). Studies of knee adduction, flexion, rotation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 76 publications
3
61
0
3
Order By: Relevance
“…It is associated with changes in local and systemic inflammatory mediators, genetic factors and innate immunity. [27]…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with changes in local and systemic inflammatory mediators, genetic factors and innate immunity. [27]…”
Section: Introductionmentioning
confidence: 99%
“…It is not only the magnitude of the load but also the location of the load that influences damage, as more damage is observed on the medial surface of the tibia [9]. Knee adduction in the gait has been associated with femoral cartilage changes, and external knee flexion has been associated with more tibial cartilage changes [10]. Obesity has been associated with increased mechanical loading on the joint, as well as altering one’s gait.…”
Section: Pathophysiology Of Osteoarthritismentioning
confidence: 99%
“…Both normal physiologic and pathologic overload forces are known to regulate cellular responses in essentially all musculoskeletal connective tissues [2]. Many previous studies revealed that alter joint loading patterns could lead to OA progression [3,4].…”
Section: Introductionmentioning
confidence: 99%